A Bibliometric Review of the Literature on Social Innovation - Cruz-Cabrera, Blasa Celerina; Valadez-Solana, Brenda Dennís; Regino-Maldonado, Juan; Acevedo-Martínez, Jorge Antonio; Ríos-Castillo, Maricela (Unidad Editorial UPTC, 2022)
Social innovation (SI) is a relatively new field of research that is generating interest in the scientific community. This article presents a bibliometric review of research on SI in the period 1971-2021. 1,796 publications were analyzed, and bibliometric methods of performance analysis and scientific mapping were handled. In the performance analysis, several bibliometric indicators were used, such as the h-index, productivity, and citations. In addition, the VOSviewer software was employed to map the bibliographic material. Scientific mapping used co-citation and keyword co-occurrence techniques. References were obtained from the Scopus database. The most relevant research in the field of SI was identified and classified, taking journals, countries, institutions, authors, and publications as units of analysis. The results showed that research in IS has increased considerably since 2009. The United Kingdom positioned itself as the most productive and influential country in this field. Sustainability Journal showed the best combination of productivity and influence in the field of SI. Frank Moulaert turned out to be the most important author of research on IS. Emerging research topics related to SI were sustainability and social entrepreneurship. JEL Codes: O31, Y10, Z00 Received: 11/02/2022.  Accepted: 14/09/2022.  Published: 01/12/2022.